2012
DOI: 10.1002/pssa.201200092
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of oxidation rates for thin films of SiGe versus Si

Abstract: In order to evaluate the role of Ge as a catalyst or inhibitor for the oxidation process in SiGe, oxidation rates for sub‐100‐nm films of SiGe are examined and compared to previous reports and established models for Si oxidation. Values for the Ge concentration in the pile‐up layer at the oxidation interface are considered as well as the more traditional approach of considering the Ge content in the as‐grown SiGe film. The experimental results presented here indicate that oxidation rates for SiGe closely match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This mechanism is thus observed for all oxidation conditions used in this study. However, depending on the oxidation temperature, three regimes of evolution of the pile up layer are distinguished and indicated on Figure 10: -For oxidation of Si0.7Ge0.3 at 900°C, the Ge concentration below the oxidation front slightly increases from 46% to 47.5% between 120 s and 540 s. The thickness also increases with time, in agreement with Long et al (11). However, contrary to their results, we found that the Ge concentration below the oxidation front depends on the initial Ge concentration.…”
Section: Ge Redistribution During Dry Rto Of Sigesupporting
confidence: 83%
See 2 more Smart Citations
“…This mechanism is thus observed for all oxidation conditions used in this study. However, depending on the oxidation temperature, three regimes of evolution of the pile up layer are distinguished and indicated on Figure 10: -For oxidation of Si0.7Ge0.3 at 900°C, the Ge concentration below the oxidation front slightly increases from 46% to 47.5% between 120 s and 540 s. The thickness also increases with time, in agreement with Long et al (11). However, contrary to their results, we found that the Ge concentration below the oxidation front depends on the initial Ge concentration.…”
Section: Ge Redistribution During Dry Rto Of Sigesupporting
confidence: 83%
“…Today, RTO is widely used in the semiconductor industry because it allows reduction of the thermal budget and fine control of the oxide thickness. Few groups studied SiGe oxidation or condensation by means of RTO (5-7) compared to furnace oxidation (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the widespread attention that has been devoted to the matter, there is still a lack of consensus regarding the oxidation kinetics of SiGe. A higher oxidation rate, often referred to as the Growth Rate Enhancement (GRE), has been reported for SiGe with respect to Si for dry oxidation [9][10][11] while other works showed no difference [12].…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24][25][36][37][38] However, conclusions about the role of Ge in determining the oxidation rate vary widely, and the Ge content at the oxidation interface is rarely characterized in a systematic way. 39 Furthermore, except for an early study using (111) oriented material, 40 oxidation of SiGe has been studied with an exclusive focus on (100) material. The orientation dependence of oxidation of Si [41][42][43] may be an indication that SiGe will exhibit similar behaviour, but it is not obvious that SiGe and Si are perfectly synonymous in this respect.…”
Section: Introductionmentioning
confidence: 99%